A Critical Interpretation on Jalaukavacharana (leech therapy) in the Management of Siragranthi: A Brief Review Study - Bandhe, Ashok Kumar; Nirmalkar, Uttam Kumar; Singh, Balendra; Normal, Satrupa (International Research Journal of Ayurveda & Yoga, 2021)
Raktamokshana (blood letting) is a karma(procedure) requiring the elimination and renovation of Dushta Rakta.(vitiated blood) Non-poisonous Jalauka (anti-poisounous leech) is used to treat arthritis, artery and venous disorders, cardiac and lung issues with varicose vein ulcers, skin conditions such as psoriasis, eczema, and hypopigmentation spots. Shira Sankocha, (contractions) Shira Vakrata, Shira utsedha(elevation) and Vishoshana(dryness) are the clinical characteristics of Siragranthi. (Varicose vein) Features are beneficial in associated Siragranthi with varicose veins. Raktamokshana (blood letting) consists of two words: Rakta and Mokshana, so that Raktamokshana (blood letting) ensures that blood is released. Treatment of medicinal leeches for conditions of sickness is termed Hirudo-therapy. Not only does Jalaukavacharana (leech therapy) drain blood from the body, but it also injects biologically active compounds that help treat multiple diseases. Jalauka (leech ) is likely to purify the body by eliminating deeply-seated toxins and pacifying the vitiated Dosha.